AN ANALYIS OF CODE SWITCHING USED BY THE ENGLISH TEACHER IN TEACHING SPEAKING TO THE ELEVENTH GRADE STUDENTS AT SMK DWIJENDRA DENPASAR IN ACADEMIC YEAR 2019/2020 - Fidelis Darung; Gede Sutrisna (Widyasrama, 2020)
This research aimed at analysing the types of code switching used by the English teacher in teaching speaking to the eleventh grade students at SMK Dwijendra Denpasar. The problem of this research was “What are the types of code switching used by the English teacher in teaching speaking at SMK Dwijendra Denpasar? This research used case study dealing with the types of code switching used by the English teacher in teaching speaking to the eleventh grade students at SMK Dwijendra Denpasar. The sources of data were words, phrases, clauses and sentences used by the teacher during teaching learning process. In collecting the data, the researcher used the following steps such as; audio recordings, video recordings and field notes. In analysing the data, the researcher used three steps; data reduction, data display and conclusion drawing. Next, the writer has collected the important data dealing with the objective of the study. There were 29 data of code switching used by the English teacher. From these data, the researcher only found three types of code switching used by the English teacher. First, inter sentential switching has twelve data, intra sentential switching has eleven data, and emblematic switching has six data.